Impact of Positive Personal Traits on University Student Engagement in Mexico, Colombia, and El Salvador - Durón-Ramos, Maria Fernanda; Mojica-Gómez, Pedro Alexis; Villamizar-Gomez, Katherine; Chacón-Andrade, Edgardo René (Frontiers in Education, 2020)
A large number of determinants influence the academic engagement of university students. However, positive influences that can be encouraged by the university have not been thoroughly studied. Most psychological research has been conducted in developed countries. Given the importance of understanding and encouraging university students in Latin America, it is essential to increase the quantity of research focused on personal traits and their association with better performance by university students. Two positive traits that have been shown to improve performance in a variety of areas are emotional intelligence and orientation to happiness. However, little is known about the relationship between these two positive aspects and university student engagement. The aim of this study was to determine the impact of emotional intelligence and orientation to happiness on university student engagement in three Latin American countries: Mexico, Colombia, and El Salvador. A total of 621 students answered a quantitative instrument that evaluates the three variables of interest. A model of structural equations was carried out in order to verify the direct impact that emotional intelligence and orientation to happiness have on university student engagement. The model explained 38% of the variance of university student engagement, indicating that these two positive personal traits can enhance interest and performance in scholarly activities by university students. Higher education in Latin America often focuses on increasing the knowledge of their students; however, these results indicate that promoting personal development, such as greater orientation towards happiness and emotional intelligence, can produce better results